Kepemimpinan Wanita Dalam Falsafah Jawa: Hasta Brata - Thomafi, Nur Asiyah Sholihah (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
Stereotypical views in society often place women as figures who are less worthy of occupying leadership positions, with the assumption that they do not have the required leadership qualities. The ancestral heritage in Javanese cultur in the form of Javanese leadership philosophy actually contains deep moral values, one of which is hastabrata. This study examines womens leadership in the Javanese philosophy of hasta brata. The method used is Library Research/literature by relying on references from various literature sources. The result is, women can lead effectively by relying on their feminine characteristics, without having to adopt a masculine style that is identical to traditional male leadership. They are accepted by society because they are able to carry out leadership roles with their own authenticity and uniqueness.